The art of breastfeeding - Carranza, Bibiana Moreno; Joyce, Jayne; Pitman, Teresa; Swisher, Anna (Ballantine Books, 2024)
"An all-new edition of the book breastfeeding mothers have relied on for generations is here! La Leche League has for many years set the standard for supporting families in the art of breastfeeding. This new edition brings that support to today's parents, with up-to-date information, new illustrations, and stories from mothers, fathers, and grandparents around the world sharing their own experiences. What's inside? Why breastfeeding matters Getting started-feeding cues and nursing positions Life with your breastfed baby Managing common challenges-new research Going back to work-expressing and storing your milk Sleep (and how to get more of it), starting family foods, and weaning La Leche League is here to help you meet your breastfeeding goals, whether you're planning to breastfeed for a few weeks or a few years. This book puts information at your fingertips, ready to help you when you need support at any point on your breastfeeding journey"--